2023
DOI: 10.1007/s11069-023-05821-5
|View full text |Cite
|
Sign up to set email alerts
|

Method for site selection of relief supply warehouses in earthquakes with Ms ≥ 7—a case study of western Yunnan, China

Abstract: Relief supply warehouses provide necessities of life for victims in disaster relief. The science behind site selection for large relief supply warehouses determines whether victims in earthquakes with Ms ≥ 7 can receive timely and effective relief. This study proposed a method of site selection for relief supply warehouses based on the prediction of earthquake disasters and the quanti cation of site selection criteria. This method considered four factors, i.e., the prediction of earthquake-prone areas, the ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was reported that during disaster response operations, first responders faced inadequate equipment supply [70]. In China, during the earthquake measuring 7.9 on the Richter scale, search and rescue operations were hampered due to limited equipment, and intervention teams were reported to have dug out survivors with their bare hands [71]. In Haiti, during the earthquake measuring 7.0 in 2010, the lack of appropriate vehicles and equipment hindered search and rescue operations [72].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that during disaster response operations, first responders faced inadequate equipment supply [70]. In China, during the earthquake measuring 7.9 on the Richter scale, search and rescue operations were hampered due to limited equipment, and intervention teams were reported to have dug out survivors with their bare hands [71]. In Haiti, during the earthquake measuring 7.0 in 2010, the lack of appropriate vehicles and equipment hindered search and rescue operations [72].…”
Section: Discussionmentioning
confidence: 99%